2016
DOI: 10.13005/ojc/320516
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Properties and Hydration Characteristics of Novel Nano-Size Mineral Trioxide and Tetracalcium Phosphate for Dental Applications

Abstract: Nano particles made of pure single phase Mineral trioxide [tricalcium silicate (C 3 S)] and Tetracalcium phosphate (TTCP) bio ceramics were prepared via solid state reaction at high temperature. Setting times, compressive strength, pH, XRD, FTIR and scanning electron microscopy (SEM) were investigated. Cytotoxicity and antibacterial activity of both C 3 S and TTCP to human gingival fibroblasts were studied. Both C 3 S and TTCP compounds undergo hydration reaction when mixed with distilled water. A delayed sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…In FTIR spectrum, absorption peaks were found at 452, 471, 502, 567, 600, 628, 958, 987, 1044, 1091, 1625, 1922, 2001, 2077, 3435, 3570 and 3643 cm −1 . As labelled in Figure 2 , PO 4 3− bands of TTCP were detected in the spectrum which were found similar with that of literature [ 43 , 44 , 45 ]. OH − stretching bands located at 628 and 3570 cm −1 indicated the presence of HA [ 42 , 46 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In FTIR spectrum, absorption peaks were found at 452, 471, 502, 567, 600, 628, 958, 987, 1044, 1091, 1625, 1922, 2001, 2077, 3435, 3570 and 3643 cm −1 . As labelled in Figure 2 , PO 4 3− bands of TTCP were detected in the spectrum which were found similar with that of literature [ 43 , 44 , 45 ]. OH − stretching bands located at 628 and 3570 cm −1 indicated the presence of HA [ 42 , 46 ].…”
Section: Resultssupporting
confidence: 90%
“…Figure 1 shows that TTCP and hydroxyapatite peaks were detected since the powder was furnace-cooled [ 9 , 37 , 42 , 43 ]. A trace amount of monetite and calcium oxide (CaO) were also found from the XRD analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This was in accordance with Guerreiro-Tanomaru et al who attributed the increase in strength to the ending of the hydration phase which might enhance the hardness of the cement material [13] . This is partially in agreement with what was found by Kim et al and Shiowaza et al, who confirmed that cement maturation continued after the first day because crosswise bonds were set in the cement matrix; but they are contradicting in the part where they stated that the acid-based reaction after one week was stable [17] [18] .…”
Section: Discussionsupporting
confidence: 92%
“…Cylindrical CPC specimens were fabricated using a cylindrical Teflon mold with a diameter of 6 mm and a height of 12 mm (Guo et al, ). The mold was filled with a cement paste, stored in a sealed container, and maintained at 37°C for 24 hr at 100% relative humidity and immersed in phosphate‐buffered saline (PBS) for 28 days for complete hydration (Radwan, El‐Hamid, & Nagi, ). The cylindrical CPC specimens after demolding were used for experiments.…”
Section: Methodsmentioning
confidence: 99%